2017
DOI: 10.3390/ijerph14020158
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Ethnic-Specific Waist-Circumference Cut-Off Points of Metabolic Syndrome among Low-Income Rural Uyghur Adults in Far Western China and Implications in Preventive Public Health

Abstract: Background: Metabolic syndrome is pandemic; however, the cut-off values for waist circumference (WC) vary widely depending on the ethnic groups studied and the criteria applied for WC measurement. Previous studies for defining optimal WC cut-off points included high-income and urban settings, and did not cover low-income, rural settings, especially for ethnic minorities. This study aimed at defining optimal ethnic-specific WC cut-off points in a low-income, rural population comprising the largest inhabitant mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
1
15
0
1
Order By: Relevance
“…However, China is a multi-ethnic country with at least 55 ethnic groups. There are few studies focused on MetS among different ethnic groups in China, and most of these studies focused on a single ethnic group [7,12,13]. The heterogeneity in study design, inclusion criteria and definition of MetS makes it difficult to compare the prevalence in different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, China is a multi-ethnic country with at least 55 ethnic groups. There are few studies focused on MetS among different ethnic groups in China, and most of these studies focused on a single ethnic group [7,12,13]. The heterogeneity in study design, inclusion criteria and definition of MetS makes it difficult to compare the prevalence in different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Controversies exist concerning the correct anthropometric values relative to ethnicity, genetic background, sex, and sociocultural context [ 11 ]. Studies have shown that WC is among the most powerful tools for predicting METs and that the optimal cut-off values for various indices, including WC, may differ by sex and race [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, our sample sizes were not adequate to explore results stratified by age. Similarly, we could not stratify by race/ethnicity, although race/ethnicity may affect the accuracy of body composition cutoffs and the association between visceral fat and health risks . Third, our sample was only 22.1% female.…”
Section: Discussionmentioning
confidence: 96%